Peluang Terjadinya Tindak Pidana Korupsi Akibat Pandemi Wabah Covid 19 - Angga Pramodya Pradhana; Meirza Aulia Chairani (Universitas Merdeka Madiun, 2021)
Corruption during the Covid 19 pandemic led to the fact that many people experienced layoffs, employee reductions and the distribution of working hours for employees. This will have an impact on reducing income or not getting more income. This income reduction will lead to a criminal act, namely the Corruption Act, to fulfill the needs of oneself, others and corporations. This will affect the economy and harm the country's finances. The method used in this research is Normative Juridical. Based on the results of research on the perpetrators of corruption during this pandemic, it is very sensitive because everyone in the world is experiencing this pandemic and some people are making personal gains, others and corporations this needs to be given severe sanctions because during the Covid 19 pandemic they committed criminal corruption contained in Article 2 and Article 3 of the PTPK Law, and the penalty is added 1/3 (one third) of the main criminal.